A Methodological Research for Development and Psychometric Properties of a New Instrument for Religious Attitudes Test on Organ Donation among Muslim Population - Sakineh Rakhshanderou; Samira Daneshvar; Morteza Abdoljabbari; Marzieh latifi; Mohtasham Ghaffari (Indian Journal of Transplantation)
Background: The absence of standard tools to measure the religious attitudes toward organ donation creates the need for new instruments, and it is important to design and to validate a scale for this purpose. The current study aims to develop and examine the psychometric properties of an instrument for religious attitudes test on organ donation (IRATOD) as a new measure in Persian language. Materials and Methods: In this methodological study, the initial version of the instrument to measure religious attitudes toward organ donation was developed through semi-structured interviews and literature review. In the second phase, psychometric evaluation followed four steps: (1) face validity (n = 20), (2) content validity (n = 10 experts), (3) construct validity by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) (n = 220), and (4) reliabilities of test–retest stability and internal consistency (n = 20). SPSS version 16 and EQS 6.4 software were used for data analysis. Results: The obtained instrument included 15 items. The average content validity ratio and content validity index were 0.81 and 0.92, respectively. Kaiser–Meyer–Olkin coefficient (>0.70) and Bartlett’s sphericity test (P < 0.001) showed that the data had a normal distribution and the sample size was ideal for factor analysis. EFA has given rise to the extraction of three factors of compatibility of organ donation with religious beliefs, beliefs about soul and body relationship, and effects of organ donation on future life explained 62.07% of the total variance. Furthermore, CFA of the items resulted in a suitable and good estimate based on the general fit indices of the model (root mean square error of approximation = 0.07, incremental fit index = 0.90, goodness of fit index [GFI] =0.89, comparative fit index = 0.93, adjusted GFI = 0.86). The Cronbach’s alpha coefficient of the 15-item IRATOD was 0.70 and for the factors in the instrument was between 0.65 and 0.90. The intraclass correlation coefficient was 0.88 interval from 0.78 to 0.94. Conclusions: The newly developed IRATOD-15 which has good psychometric properties can be useful for shedding light on the organ donation-related attitudes and beliefs of populations in researches with various designs such as formative and interventional.